Postnatal impoverished housing impairs adolescent risk-assessment and increases risk-taking: A sex-specific effect associated with histone epigenetic regulation of Crfr1 in the medial prefrontal cortex. (January 2019) - Viola, Thiago Wendt; Wearick-Silva, Luis Eduardo; Creutzberg, Kerstin C.; Kestering-Ferreira, Érika; Orso, Rodrigo; Centeno-Silva, Anderson; Albrechet-Souza, Lucas; Marshall, Paul R.; Li, Xiang; Bredy, Timothy W.; Riva, Marco A.; Grassi-Oliveira, Rodrigo
Highlights: Impoverished housing impairs risk-assessment and risk-taking in females. Decreased HPA axis responsivity in females exposed to impoverished housing. Crfr1 mRNA levels in the mPFC correlated with risk-taking. Crfr1 gene expression is dynamically altered during risk-taking processing. Histone alteration within the promoter of Crfr1 contributes to such effect. Abstract: While increasing evidence posits poor decision-making as a central feature of mental disorders, very few studies investigated the effects of early-life stress (ELS) on specific components of reward-related choice behaviors. Risk-taking (RT) involves the exposure to some danger, or negative consequences, in order to achieve a goal-directed behavior. Such behaviors are likely to be preceded by risk-assessment (RA), which is a dynamic cognitive process involving the acquisition of information in potentially dangerous situations. Here, we investigated the effects of being raised in impoverished housing conditions during early life (P2–P9) on RT, RA and dopaminergic and corticotrophinergic gene expression of adolescent male and female mice. Phenotypes were assessed by two protocols: the elevated plus-maze (EPM) and the predator-odor risk-taking (PORT). We found decreased RA in mice exposed to impoverished housing in the absence of a reward (EPM), with a more pronounced effect among females. Moreover, when exposed to a predatory olfactory cue, increased RT was observed in these females in a reward-related task (PORT), as well as decreased HPA axis responsivity. This sex-specific behavioral effect was associated with increased Crfr1 mRNA expression in the medial prefrontal cortex (mPFC) and higher levels of the histone mark H3R2 me2s, a histone modification known to be involved in transcriptional activation, within the promoter of the Crfr1 gene. These findings revealed that ELS exposure can impair the acquisition of environmental information in dangerous situations and increase RT in reward-related scenarios among females, with an important role regarding epigenetic regulation of the Crfr1 gene.